The correlation of consuming thymoquinone extract of nigella sativa to tooth socket re-epithelization on diabetic-induced rats - Mei Syafriadi; Putri R. Yusuf; Sabrina M. Pratama; Dina Z. Ummah; Khoirul Amalia (Journal of Dentomaxillofacial Science, 2018)
Objective: The purpose of this research is to determine the effect of Tq to re-epithelialization at the margin of tooth socket post-extraction in diabetic rats.Material and Methods: Used 27 rats were induced diabetic with streptozotocin (STZ) dose of 50 mg/kg body weight of rats which divided into 3 groups that has been stained with hematoxillin-eosin and cytokeratin 19. They are P1 treated with thymoquinone (Tq), P2 treated with metformin, and K without treatment. Each group consist of 9 rats were divided into 3 subgroups based on day of observation. They are 3rd, 7th and 10th day post-extraction. Re-epithelialization was observed at the margin of the tooth socket that has been stained with hematoxillin-eosin and cytokeratin 19Results: showed there was an improvement of re epithelialization percentage in the Tq treatment group compared with P2 and K groups.Conclusion: Thymoquinone extract may decrease blood glucose level and increasing re-epithelialization in margin of the tooth socket after extraction in diabetic rats.